(untitled) - James R Hurford (New York, 1995)
This coursebook has been carefully planned to introduce students to all the main elements of semantics in a simple, step-by-step fashion. Each unit of the course includes short sections of explanation and examplification followed by stimulating practice exercises for the sudents to comlpete. Sections of answerss and comment inable students accurately to monitor their progress trough the course
Keywords: semantics